2023
DOI: 10.1021/acs.chemmater.2c03540
|View full text |Cite
|
Sign up to set email alerts
|

Ferroaxial Transitions in Glaserite-type Compounds: Database Screening, Phonon Calculations, and Experimental Verification

Abstract: The so-called ferroaxial transition characterized by a rotational structural distortion that breaks a mirror symmetry has gained growing interest in terms of a new class of ferroic state in crystalline materials. RbFe(MoO 4 ) 2 , which belongs to glaseritetype compounds, X (□;1) Y (□;2) [M(TO 4 ) 2 ], is one of the most representative materials showing a ferroaxial transition, i.e., ferroaxial materials. Considering a variety of glaserite-type compounds, we expect that they provide a good arena for ferroaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To realize the ferroaxial order in crystalline materials, the “staggered structure”, where the nonequivalent coordination polyhedra are alternately connected, is required. Representative examples of such staggered structures in crystalline materials are the ordered-double or charge-ordered perovskite structure [Figure b] and a corner-sharing alternate structure of octahedra and tetrahedra (e.g., glaserite structure , ) [Figure c]. In these staggered structures, the magnitude of A i is no longer identical at neighboring polyhedra.…”
Section: Conceptsmentioning
confidence: 99%
“…To realize the ferroaxial order in crystalline materials, the “staggered structure”, where the nonequivalent coordination polyhedra are alternately connected, is required. Representative examples of such staggered structures in crystalline materials are the ordered-double or charge-ordered perovskite structure [Figure b] and a corner-sharing alternate structure of octahedra and tetrahedra (e.g., glaserite structure , ) [Figure c]. In these staggered structures, the magnitude of A i is no longer identical at neighboring polyhedra.…”
Section: Conceptsmentioning
confidence: 99%
“…A recent study on formula-based database screening using a regular expression search and symmetry detection algorithm predicted seven glaserite-type compounds as candidates for ferroaxial materials showing a pure ferroaxial transition. 15 It was experimentally demonstrated that one of them, K 2 Zr(PO 4 ) 2 , indeed shows a ferroaxial transition at about 700 K. 15 Thus, the glaserite-type compounds are promising platforms for searching for materials showing a pure ferroaxial transition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 These forms of progress have motivated studies for developing new ferroaxial materials and controlling the ferroaxial order. 14 More recently, it has been proposed that "staggered structure", with the nonequivalent coordination polyhedra connected alternately, is essential to the emergence of ferroaxial order. 15 Rotational distortions in crystalline materials with staggered structures induce ferroaxial order, which is ascribed to ferri-like arranged electric toroidal moments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the presence of ferroaxial order has been experimentally demonstrated by visualizing the ferroaxial domains with measurements of second harmonic generation , and electrogyration . These forms of progress have motivated studies for developing new ferroaxial materials and controlling the ferroaxial order …”
Section: Introductionmentioning
confidence: 99%